Device Fabrication for Creating Multiscale Miniature Neuronal Networks and Spatiotemporal Pattern Analysis of Spontaneous Electrical Activities. Issue 2 (February 2015) - Yoshida, Lui; Kotani, Kiyoshi; Jimbo, Yasuhiko
SUMMARY To investigate the dynamics of neuronal networks, a device which is capable of multipoint simultaneous measurement and multiscale miniature neuronal network construction was fabricated. The results of culturing rat embryo hippocampal neurons showed that the device is biocompatible and can be successfully used in long‐term culture. Analysis of the electrical data obtained with the device suggested that, in miniature neuronal networks consisting of about 2000 neurons, there occurred spatiotemporal activity patterns of neurons, which were considered to be very important to the process of storing and transforming information of a brain.